New trends in financial engineering : works under the auspices of the World Class University Program of Ajou University - Koo, Hyeng Keun (Studies in probability, optimization, and statistics, 2011)
Financial engineering is defined as the application of mathematical methods to the solution of problems in finance. The recent financial crisis raised many challenges for financial engineers: not only were financially engineered products such as collateralized debt obligations and credit default swaps implicated in causing the crisis, but the risk management techniques developed by financial engineers appeared to fail when they were most desperately needed. This book is the first in a series describing research by a multidisciplinary team of economists, mathematicians and control theorists exp.